"Effect of p-aminosalicylic acid rare earth complex on aging resistance of natural rubber" - "LIU Yong-gang1,2, HAO Wei2, LIU Zhao-gang2, WANG Xiao-li1, MA Sheng-mei1, ZHANG Shi-zhong1, ZHANG Feng-long1" (Hecheng xiangjiao gongye)
Natural rubber (NR) vulcanizates were prepared using rare earth antioxidants, such as lanthanum aminosalicylate (PAS-La), cerium aminosalicylate (PAS-Ce), lanthanum and cerium aminosalicylate (PAS-La-Ce), and hindered phenolic antioxidant 2246, respectively, the protective effects of four types of antioxidants on NR thermal-oxidative aging were compared by hardness, tensile properties, thermogravimetric analysis, and infrared spectroscopy, and Kissinger method and Flynn-Wall-Ozawa method were used to analyze the thermal-oxidative aging behavior of NR vulcanizates without antioxidant and with four kinds of antioxidants. The results showed that the protective effect of rare earth antioxidants was better than that of hindered phenolic antioxidant 2246, the retention rates of mechanical properties of PAS-La/NR, PAS-Ce/NR, and PAS-La-Ce/NR vulcanizates were higher than those of 2246/NR vulcanizate with PAS-La-Ce/NR vulca-nizate having the highest mechanical properties retention rate and PAS-La having the best protective effect. During the thermal-oxidative aging process, all five types of NR vulcanizates underwent oxidation reactions, the addition of rare earth antioxidants and hindered phenolic antioxidants 2246 could increase the activation energy required for the thermal-oxidative degradation of NR and enhance the thermal oxidative stability of NR, and the thermal-oxidative aging resistance of PAS-La/NR and PAS-Ce/NR vulcanizates was superior to that of antioxidant 2246/NR vulcanizate, while the thermal-oxidative aging resistance of PAS-La-Ce/NR vulcanizate was similar to that of antioxidant 2246/NR vulcanizate.